2017
DOI: 10.1037/fam0000299
|View full text |Cite
|
Sign up to set email alerts
|

Military children’s difficulty with reintegration after deployment: A relational turbulence model perspective.

Abstract: This study drew on the relational turbulence model to investigate how the interpersonal dynamics of military couples predict parents' reports of the reintegration difficulty of military children upon homecoming after deployment. Longitudinal data were collected from 118 military couples once per month for 3 consecutive months after reunion. Military couples reported on their depressive symptoms, characteristics of their romantic relationship, and the reintegration difficulty of their oldest child. Results of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Just as our study sought to document the trajectory of reintegration difficulty among returning service members and at‐home partners, knowledge gaps exist about how military children experience a parent's homecoming (Meadows et al, ). Both parental mental health (Chandra et al, ) and marital processes (Knobloch, Knobloch‐Fedders, Yorgason, Ebata, & McGlaughlin, ) are likely to play a role in military children's outcomes. Subsequent work that builds on our findings would be helpful for continuing to identify data‐driven recommendations to support military families during the postdeployment transition.…”
Section: Discussionmentioning
confidence: 99%
“…Just as our study sought to document the trajectory of reintegration difficulty among returning service members and at‐home partners, knowledge gaps exist about how military children experience a parent's homecoming (Meadows et al, ). Both parental mental health (Chandra et al, ) and marital processes (Knobloch, Knobloch‐Fedders, Yorgason, Ebata, & McGlaughlin, ) are likely to play a role in military children's outcomes. Subsequent work that builds on our findings would be helpful for continuing to identify data‐driven recommendations to support military families during the postdeployment transition.…”
Section: Discussionmentioning
confidence: 99%
“…RTT accounts for the interactive nature of relationships, but it often prioritizes the individual as the unit of analysis; for example, RTT often highlights the role individual perceptions play in shaping relational outcomes such as collaborative planning and support. However, the past dyadic work using the relational turbulence perspective has uncovered partner effects, indicating that the perceptions of an individual impact their relational partner and the relationship (Knobloch, Knobloch-Fedders, Yorgason, Ebata, & McGlaughlin, 2017; McLaren & Solomon, 2014; Theiss & Nagy, 2010). For instance, in their work on sexual intimacy in married couples, Theiss and Nagy (2010) found that an individual’s sexual satisfaction was negatively associated with their spouse’s reports of relational uncertainty and interference from a partner.…”
Section: A Relational Turbulence Perspectivementioning
confidence: 99%
“…Quantitative data have documented relational uncertainty and interference from a partner as predictors of people's appraisals of relational turbulence (Knobloch, McAninch, et al, 2016; Theiss & Knobloch, ), their relationship satisfaction (Knobloch & Theiss, ), and their communication behavior (Knobloch, Ebata, McGlaughlin, & Theiss, ; Knobloch & Theiss, ; Theiss & Knobloch, ) during the postdeployment transition. With respect to outcomes specific to the transition itself, work has revealed relational uncertainty and interference from a partner as predictors of military couples' own difficulty with reintegration (Knobloch, Ebata, McGlaughlin, & Ogolsky, ) and their children's difficulty with reintegration (Knobloch et al, ). These findings, viewed as a set, imply that relational turbulence theory has promise for illuminating the experiences of military couples and families upon reunion following deployment.…”
Section: Relational Turbulence During Reintegrationmentioning
confidence: 99%
“…Observations gathered over time are critical for evaluating the dynamic processes articulated by relational turbulence theory in a trio of ways. First, the only longitudinal project published to date contained only three waves of data (see Knobloch, Ebata, McGlaughlin, & Ogolsky, ; Knobloch, Ebata, McGlaughlin, & Theiss, ; Knobloch et al, ; Knobloch, McAninch, et al, 2016), so a lingering task is to track the postdeployment transition across the 6 months typically ascribed to reintegration (Pincus et al, ). A second benefit of collecting more waves of data over a longer period of time is the capacity to disentangle reciprocal effects in the pathways posed by the theory (e.g., Knobloch & Theiss, ).…”
Section: Suggestions For Researchmentioning
confidence: 99%
See 1 more Smart Citation